ALLELOPATHICPOTENTIAL OF WATEREXTRACTOF PARTS FOR TWO APPLE FRUIT VARIETIESONGERMINATIONAND GROWTH SOME ORNAMENTAL PLANTS - Salah M. Saied (Mesopotamia Journal of Agriculture)
This research was conducted in green house of Department of Biology/ College of Science/ Mosul University to study the effect of water extracts for green and red apples for their three parts (peal 4%. pith 8% and fruit 12%) to soil in germination and some growth characteristics for the three kinds of ornamental plants which grow in this soil.The results showed that there is a decrease in most of the characteristics of Viola wittrockiana andCalendula officinalis plants except the concentration of the elements potassium and phosphorous where they led to an increase in most of the elements concentration in their leaves. Otherwise. we noticed that there is a differencebetween inhibition and stimulation in some growth characteristics for Mathiolaincana with other plants and control treatment. While concerning the effect of the kinds.the red apple was more inhibitive than green apple. In respect of the other parts. the pith was much effective in most characteristics and the least effect was in the fruit. It was shown also thatViola wittrockiana and Calendula officinalis plants were more sensitive when treating with extracts. while Mathiolaincana gave better growth.